Functional characterization of a gamma-glutamyl phosphate reductase ProA in proline biosynthesis and promoting expression of type three secretion system in Ralstonia solanacearum - Guan, Yue; Wang, Rongsheng; Chen, Nan; Zhu, Yalan; Han, Liangliang; Chen, Xinping; Li, Jing; Zhang, Yong (Frontiers in Microbiology, 2022)
Ralstonia solanacearum RSc2741 has been predicted as a gamma-glutamyl phosphate reductase ProA catalyzing the second reaction of proline formation from glutamate. Here, we experimentally demonstrated that proA mutants were proline auxotrophs that failed to grow in a minimal medium, and supplementary proline, but not glutamate, fully restored the diminished growth, confirming that ProA is responsible for the biosynthesis of proline from glutamate in R. solanacearum. ProA was previously identified as one of the candidates regulating the expression of genes for type three secretion system (T3SS), one of the essential pathogenicity determinants of R. solanacearum. Supplementary proline significantly enhanced the T3SS expression both in vitro and in planta, indicating that proline is a novel inducer of the T3SS expression. Deletion of proA substantially impaired the T3SS expression both in vitro and in planta even under proline-supplemented conditions, indicating that ProA plays additional roles apart from proline biosynthesis in promoting the expression of the T3SS genes. It was further revealed that the involvement of ProA in the T3SS expression was mediated through the pathway of PrhG-HrpB. Both the proA mutants and the wild-type strain grew in the intercellular spaces of tobacco leaves, while their ability to invade and colonize tobacco xylem vessels was substantially impaired, which was about a 1-day delay for proA mutants to successfully invade xylem vessels and was about one order of magnitude less than the wild-type strain to proliferate to the maximum densities in xylem vessels. It thus resulted in substantially impaired virulence of proA mutants toward host tobacco plants. The impaired abilities of proA mutants to invade and colonize xylem vessels were not due to possible proline insufficiency in the rhizosphere soil or inside the plants. All taken together, these results extend novel insights into the understanding of the biological function of ProA and sophisticated regulation of the T3SS and pathogenicity in R. solanacearum.